SPEED and VELOCITY in Arabic and English: A Corpus-based Cognitive Linguistic Analysis - Hicham Lahlou, Hajar Abdul Rahim (International Journal of Advanced Science and Technology, 2020)
Current research shows that the gap between scientific knowledge and everyday knowledge may impede students’ learning of science. The present study aims at investigating the terms denoting the concepts of speed and velocity in Arabic and English in terms of meaning, prototypicality, conceptual metaphor and conceptual metonymy based on Lakoff’s (1987) idealized cognitive models (ICMs). The data for analysis was extracted from Arabic and English dictionaries as well as corpora. The results show that Arabic سُرْعَة (speed) and English speed overlap and contrast in terms of meaning extension and its motivation, and overlap in prototype, scale. The dominance of scale in conceptualizing the terms may cause both Arabic and English speakers to confuse speed and velocity if they are not alerted to the difference between their prior knowledge and scientific meanings of the terms. These results have important implications for research in linguistics and science education.